Human resource management in sports institutions - zaouk, mhamed (sports creativity, 2025)
This study aimed to identify human resources in sports institutions through organizational levels and their management and monitoring stages, as well as to highlight the importance of the human element as a factor in the success of sports institutions, in light of the economic transformations that various institutions have experienced.